Teacher Guidance in the Digitalization Era: Efforts to Improve Student Achievement by Strengthening Online Sourced Learning Materials - Abd. Basir; Salamah; Suriagiri; Mudhiah; Mohammad Ahmad Bani Amer (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The article aimed to analyze the teacher guidance in the digitalization era: an effort to improve student achievement by strengthening online-sourced learning materials at Madrasah Aliyah Negeri (MAN) Insan Cendikia Pelaihari Banjarmasin. Through semi-structured interviews with several teacher councils, the researchers have received many vital inputs regarding the dedication of teachers in guiding students to learn applications in the digital era in the distance learning situation. The researchers used a phenomenological approach to understand how teachers monitor online learning activities in the current era of technology. The result showed that the teachers was able to get the students care and using learning resources in various forms of application. The dedication of the teachers and the students in Madrasah Aliyah teachers from Pelaihari Banjarmasin has become strengthening in online sourced learning materials. The stduents has changed to get learning achievement to be better result. Hopefully, these findings help developing educational studies in the current era of technology. Keywords: Online Learning Materials, Improve Students Achievement, Online Learning